The Problems of Implementation of Financial Services Authority Regulation No. 11/POJK.03/2020 in Relation to Legal Awareness and Legal Compliance of Bank Mandiri MSME Debtors - Mompang Panggabean; Benny Hutahayan (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The spread of Corona Virus Disease 2019 has disrupted the economy so that it has an impact on increased bank credit risk due to decreased performance and capacity of debtors in fulfilling credit or financing payment obligations. The Financial Services Authority (FSA) issued FSA Regulation No. 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of COVID-19 so that the pandemic does not have an impact on the domestic economy, including MSMEs. The goal is to provide credit relaxation for customers affected by Covid-19. This research aims to examine the effect of Legal Substance and Legal Awareness on the legal compliance of MSMEs as customers of Bank Mandiri. This research used a questionnaire as the research instrument. The questionnaire was used to measure the variables of Legal Substance, Legal Awareness and Legal Compliance. The data analysis used is the SEM GSCA approach using the GeSCA application. The results of the analysis showed that legal substance and legal awareness have a significant effect on legal compliance. The legal analysis of the substance of FSA Regulation Number 11/POJK.03/2020 in Indonesia for Bank Mandiri MSME debtors is the originality of this research.